Collaborative detection and on-line monitoring of pipeline stress in oil and gas stations. (1st October 2022) - Zhao, Jianhua; Liao, Kexi; Li, Xiaoxiao; He, Guoxi; Xia, Feng; Zeng, Qiang
Abstract: The types of pipeline used in oil and gas stations is diverse, and it is difficult to comprehensively and accurately measure pipeline stress using a single detection method. Non-contact pipeline magnetic detection (NPMD), metal magnetic memory, ultrasonic stress measurement (USM) and ultrasonic thickness measurement (UTM)constitute a collaborative detection strategy for station pipelines. The pipeline magnetic abnormal evaluation parameter N is derived according to the sensor arrangement in NPMD devices. The magnetic field distribution based on different extraction heights is determined by the magnetic charge model and the experimental results, and a feature parameter E is constructed that can characterize the degree of stress concentration. The pipeline stress concentration points can be quickly determined in accordance with N and E . Reference stress values can be measured using USM and UTM. Monitoring is implemented at the stress concentration points, and the true stress values at the stress concentration points of the pipeline are established by combining the stress detection results. The collaborative detection method is applied to an oil and gas station, and two stress concentrations of 186.7 and 211.6 MPa are identified, respectively. The stress at the excavation pit is confirmed to be 196 MPa based on the monitoring data. Based on collaborative detection and on-line monitoring, fast and efficient collaborative detection and real-time mastering of station pipeline stress are achieved.